Development of a Metal Craft Learning Package Based on Local Ornamental Motifs for Extracurricular Students - Sarifudin Sarifudin; Erna Anggraini; Galih Suryadmaja (Journal La Edusci, 2026)
This study aimed to develop and evaluate a metal craft learning package based on local ornamental motifs for students participating in extracurricular visual arts activities at SMK Negeri 2 Makassar. The study employed a Research and Development approach adapted from the Borg and Gall model and organized into three phases: needs analysis, product development, and evaluation. The learning package consisted of a teacher’s guidebook, student handbook, metal craft textbook, presentation media, and student creativity assessment instrument. The participants were 32 extracurricular students. Data were collected through observations, interviews, expert-validation questionnaires, student-response questionnaires, creativity assessments, and documentation. Quantitative data were analyzed descriptively using mean scores and a five-point conversion scale, while qualitative data were analyzed through classification, interpretation, and conclusion drawing. The material expert validation produced an overall mean score of 4.31, while the media expert validation obtained 4.23, both categorized as excellent. The one-to-one, small-group, and large-group trials yielded overall mean scores of 4.55, 4.43, and 4.45, respectively, indicating a high level of practicality. Observations and participant responses showed that the visual examples, step-by-step procedures, and local motif illustrations helped students understand design development, repoussé techniques, and artwork-finishing stages more systematically. In the large-group trial, the mean student creativity score reached 84, exceeding the Minimum Mastery Criterion of 75. These findings indicate that the developed learning package met the criteria of validity, practicality, and effectiveness and was suitable for supporting local culture-based metal craft learning in extracurricular activities.